2004
DOI: 10.1007/s00464-003-9322-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased peritoneal dissemination after laparotomy versus pneumoperitoneum in a mouse cecal cancer model

Abstract: Peritoneal dissemination was more extensive after laparotomy than after CO(2) pneumoperitoneum in a mouse model of cecal cancer with serosal invasion. Decreased expression of E-cadherin mRNA in tumors after laparotomy, but not after CO(2) pneumoperitoneum, may be associated with the increase in peritoneal dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
1
3
0
2
Order By: Relevance
“…Some experimental studies have reported greater tumor progression after laparotomy than after pneumoperitoneum [3,10,18]. Our results also suggested such a response because laparotomy allowed greater tumor growth than CO 2 pneumoperitoneum.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Some experimental studies have reported greater tumor progression after laparotomy than after pneumoperitoneum [3,10,18]. Our results also suggested such a response because laparotomy allowed greater tumor growth than CO 2 pneumoperitoneum.…”
Section: Discussionsupporting
confidence: 70%
“…These results have encouraged the use of laparoscopy for oncologic procedures, but controversies about the risk of metastases and tumor progression still remain [20]. In experimental models, laparoscopy promoted less tumor dissemination than laparotomy [18]. Natural killer activity (NKA) exerts a first-line defense mechanism against tumor progression [2].…”
mentioning
confidence: 98%
“…In addition, early research has suggested potential factors that lead to an increase in recurrence rates with the laparoscopic approach. For example, abdominal insufflation with carbon dioxide is believed to foster tumor growth and peritoneal dissemination ( 35 , 36 ). In our study, all included patients used uterine manipulators during LRH, and all colpotomies were performed intracorporeally in accordance with the traditional international consensus.…”
Section: Discussionmentioning
confidence: 99%
“…El papel del neumoperitoneo en la diseminación celular intraperitoneal durante la cirugía laparoscópica es un tema por resolver y que ha generado abundante bibliografía desde los inicios de la aplicación de esta tecnología en el tratamiento de la patología intraabdominal, especialmente desde el punto de vista oncológico. Tras el auge de los procedimientos laparoscópicos acaecido en los últimos decenios del siglo pasado, la controversia respecto a la conveniencia de implementar dicho avance tecnológico en el tratamiento de la patología neoplásica no ha cesado (Hernández Lizoain, J.L., 1999;Takeuchi, H., 2004).…”
Section: Discusión 171unclassified
“…Dicho efecto sería más evidente a una mayor presión del gas. De hecho, Takeuchi, en un modelo experimental de diseminación neoplásica peritoneal, evidencia que ésta es mayor en el grupo de laparotomía que en el de laparoscopia (Takeuchi, H., 2004), datos apoyados por estudios posteriores (Kagohara,O.H., 2012).…”
Section: Discusión 173unclassified